Comparative Prognostic Utility of Indexes of Microvascular Function Alone or in Combination in Patients With an Acute ST-Segment–Elevation Myocardial Infarction. Issue 23 (6th December 2016) - Carrick, David; Haig, Caroline; Ahmed, Nadeem; Carberry, Jaclyn; Yue May, Vannesa Teng; McEntegart, Margaret; Petrie, Mark C.; Eteiba, Hany; Lindsay, Mitchell; Hood, Stuart; Watkins, Stuart; Davie, Andrew; et al.
Abstract : Background: Primary percutaneous coronary intervention is frequently successful at restoring coronary artery blood flow in patients with acute ST-segment–elevation myocardial infarction; however, failed myocardial reperfusion commonly passes undetected in up to half of these patients. The index of microvascular resistance (IMR) is a novel invasive measure of coronary microvascular function. We aimed to investigate the pathological and prognostic significance of an IMR>40, alone or in combination with a coronary flow reserve (CFR⩽2.0), in the culprit artery after emergency percutaneous coronary intervention for acute ST-segment–elevation myocardial infarction. Methods: Patients with acute ST-segment–elevation myocardial infarction were prospectively enrolled during emergency percutaneous coronary intervention and categorized according to IMR (⩽40 or >40) and CFR (⩽2.0 or >2.0). Cardiac magnetic resonance imaging was acquired 2 days and 6 months after myocardial infarction. All-cause death or first heart failure hospitalization was a prespecified outcome (median follow-up, 845 days). Results: IMR and CFR were measured in the culprit artery at the end of percutaneous coronary intervention in 283 patients with ST-segment–elevation myocardial infarction (mean±SD age, 60±12 years; 73% male). The median IMR and CFR were 25 (interquartile range, 15–48) and 1.6 (interquartile range, 1.1–2.1), respectively. An IMR>40 was a multivariable associate of myocardial hemorrhage (odds ratio, 2.10; 95% confidence interval, 1.03–4.27; P =0.042). An IMR>40 was closely associated with microvascular obstruction. Symptom-to-reperfusion time, TIMI (Thrombolysis in Myocardial Infarction) blush grade, and no (⩽30%) ST-segment resolution were not associated with these pathologies. An IMR>40 was a multivariable associate of the changes in left ventricular ejection fraction (coefficient, −2.12; 95% confidence interval, −4.02 to −0.23; P =0.028) and left ventricular end-diastolic volume (coefficient, 7.85; 95% confidence interval, 0.41–15.29; P =0.039) at 6 months independently of infarct size. An IMR>40 (odds ratio, 4.36; 95% confidence interval, 2.10–9.06; P <0.001) was a multivariable associate of all-cause death or heart failure. Compared with an IMR>40, the combination of IMR>40 and CFR⩽2.0 did not have incremental prognostic value. Conclusions: An IMR>40 is a multivariable associate of left ventricular and clinical outcomes after ST-segment–elevation myocardial infarction independently of the infarction size. Compared with standard clinical measures of the efficacy of myocardial reperfusion, including the ischemic time, ST-segment elevation, angiographic blush grade, and CFR, IMR has superior clinical value for risk stratification and may be considered a reference test for failed myocardial reperfusion. Clinical Trial Registration: URL:https//www.clinicaltrials.gov . Unique identifier: NCT02072850. Abstract : Supplemental Digital Content is available in the text.